2019
DOI: 10.1136/bmjopen-2019-031438
|View full text |Cite
|
Sign up to set email alerts
|

Can implementation failure or intervention failure explain the result of the 3D multimorbidity trial in general practice: mixed-methods process evaluation

Abstract: ObjectivesDuring a cluster randomised trial, (the 3D study) of an intervention enacting recommended care for people with multimorbidity, including continuity of care and comprehensive biennial reviews, we examined implementation fidelity to interpret the trial outcome and inform future implementation decisions.DesignMixed-methods process evaluation using cross-trial data and a sample of practices, clinicians, administrators and patients. Interviews, focus groups and review observations were analysed thematical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 40 publications
2
53
0
Order By: Relevance
“…Intervention failure was not a problem here as it has been with other interventions. 19 Co-creation of the intervention, as in Mercer et al , 15 or provider creation, as in the present study, appear to avoid implementation lapses.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Intervention failure was not a problem here as it has been with other interventions. 19 Co-creation of the intervention, as in Mercer et al , 15 or provider creation, as in the present study, appear to avoid implementation lapses.…”
Section: Discussionsupporting
confidence: 65%
“…The current study advances on previous work by testing an intervention that should enhance everyday practice. This intervention should overcome the problem of implementation lapses found in other studies, 19 because it was provider created, which goes even further than a co-created intervention. 15 The lack of impact on outcomes for patients with an income of <C$50 000 contrasts with Mercer et al ’s 15 multifaceted intervention, which was effective for patients who were considered to be socioeconomically deprived; they focused on self-management support, more face-to-face time with patients, and continuity of care — aspects of care that could enhance follow-up to the TIP programme.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Using Normalisation Process Theory enabled us to gain important new insights on G-AP implementation which will inform the development of the G-AP training and implementation strategies, thus optimising the chances of future implementation success. Distinguishing between implementation failure and intervention failure is an important aspect of clinical practice and clinical trials [57]. We believe that this study is essential preparatory work to increase the adoption of G-AP in clinical settings and reduce the chances of implementation failure in our planned evaluation.…”
Section: Build In Ongoing Local Monitoring Evaluation and Tailoring mentioning
confidence: 93%
“…Moreover, the 3D trial process evaluation identified inadequate intervention fidelity and provider training on patient engagement as factors contributing to their modest results. 22 A 2018 scoping review further contributed by identifying the patient/professional/organizational elements (e.g., face-to-face clinical assessments, tailored interventions, provider education/meetings) that were included in effective multimorbidity interventions. 23 Since all interventions in the scoping review were complex and involved between four and eight elements, it was not possible to isolate one component to link to the success of the intervention.…”
Section: Introductionmentioning
confidence: 99%